2019
DOI: 10.1177/2331216519876795
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction of Head and Gaze Control With Acoustic Beam Width of a Simulated Beamformer in a Two-Talker Scenario

Abstract: Superdirectional acoustic beamforming technology provides a high signal-to-noise ratio, but potential speech intelligibility benefits to hearing aid users are limited by the way the users move their heads. Steering the beamformer using eye gaze instead of head orientation could mitigate this problem. This study investigated the intelligibility of target speech with a dynamically changing direction when heard through gaze-controlled (GAZE) or head-controlled (HEAD) superdirectional simulated beamformers. The be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
(53 reference statements)
2
13
1
Order By: Relevance
“…In another study [13], an eye-gaze steering HA was found to be able to improve the speech intelligibility for HI listeners compared to non-steering one. Similar results could also be found in other studies [11], [15].…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…In another study [13], an eye-gaze steering HA was found to be able to improve the speech intelligibility for HI listeners compared to non-steering one. Similar results could also be found in other studies [11], [15].…”
Section: Introductionsupporting
confidence: 92%
“…Therefore, when the auditory attended target switches between talkers, the listener would saccade and rotate head to direct the eye-gaze accordingly [7], [8]. Based on these studies, eye-gaze was treated as an indicator of the attended target and used to steer HAs [9]- [15]. For example, an eye-tracker-based eye-gaze selection of auditory target was reported to outperform the button-pressing-based manual selection, for both the measurement of target recalling and switching time [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate that the participant groups had a similar gaze-related self-motion, or that the measures are not sensitive enough to detect differences. In accordance with the results of Lu et al (2021) and Hládek et al (2019) , the participants used a combination of head and eye movements to look at the target. The significant differences in HeadGazeRatio that were found between the NH and HI participant groups indicate that the HI participants covered a larger part of the movement with head turns compared to NH participants.…”
Section: Discussionmentioning
confidence: 87%
“…When visual cues are present, listeners are less likely to turn one ear to the target speaker in order to increase SNR ( Grange et al, 2018 ). Moreover, it has been shown that while gaze movements accurately follow the target speaker location, head movements tend to undershoot the target location ( Hendrikse et al, 2018 ; Hendrikse et al, 2019a ; Hládek et al, 2019 ; Lu et al, 2021 ). Hendrikse et al (2019a) also found differences between younger and older normal-hearing participants in the relative amount of movement that was done with the head and the eyes (head-eye ratio).…”
Section: Introductionmentioning
confidence: 99%